The Ambulatory Medical Assistance (AMA) programme during active‐phase treatment in patients with haematological malignancies: A cost‐effectiveness analysis. (27th September 2022) - Michallet, Anne‐Sophie; Malartre, Stephanie; Vignaud, Elodie; Bocquet, Alexiane; Sontag, Pascale; Galvez, Christelle; Blay, Jean‐Yves; Heudel, Pierre; Vimont, Alexandre; Blachier, Martin; Ferrua, Marie; Minvielle, Etienne; et al.
Abstract: Context: The need for patient navigator is growing, and there is a lack of cost evaluation, especially during survivorship. Objective: The objective of this study is to evaluate the cost‐effectiveness of an Ambulatory Medical Assistance (AMA) programme in patients with haematological malignancies (HM). Design: A cost‐effectiveness analysis of the AMA programme was performed compared to a simulated control arm. Setting: An interventional, single‐arm and prospective study was conducted in a French reference haematology–oncology centre between 2016 and 2020. Participants: Adult patients were enrolled with histologically documented malignant haematology, during their active therapy phase, and treated either by intravenous chemotherapy or oral therapy. Methods: An extrapolation of the effectiveness was derived from a similar nurse monitoring programme (CAPRI study). Cost effectiveness of the programme was evaluated through adverse events of Grade 3 or 4 avoided in different populations. Results: Included patient ( n = 797) from the AMA programme were followed during 125 days (IQR: 0–181), and adverse events (Grade 3/4) were observed in 10.1% of patients versus 13.4% in the simulated control arm. The overall cost of AE avoided was estimated to €81, 113, leading to an ICER of €864. Conclusion: The AMA programme was shown to be cost‐effective compared to a simulated control arm with no intervention.